Infiltration of LPAR5+ macrophages in osteosarcoma tumor microenvironment predicts better outcomes - He, Yi; Zhou, Haiting; Huang, Xiaojian; Qu, Yunkun; Wang, Yingguang; Pei, Wenbin; Zhang, Rui; Chen, Sheng; You, Hongbo (Frontiers in Immunology, 2022)
Introduction Tumor microenvironment (TME) has been shown to be extensively involved in tumor development. However, the dynamic change of TME components and their effects are still unclear. Here, we attempted to identify TME-related genes that could help predict survival and may be potential therapeutic targets. Methods Data was collected from UCSC Xena and GEO database. ESTIMATE and CIBERSORT algorithms were applied to estimate the components and the proportions of TIICs in TME. We analyzed the gene expression differences of immune components and stromal components, respectively, and finally got the overlapped DEGs. Through protein-protein interaction (PPI) network and univariate Cox regression analysis based on shared DEGs, we screened out and validated the TME-related genes. Focusing on this gene, we analyzed the expression and prognostic value of this gene, and investigated its relationship with immune cells by correlation analysis, single cell analysis, immunohistochemistry and immunofluorescence analysis. Results Through a series analysis, we found that the proportion of immune and stromal components was an important prognostic factor, and screened out a key gene, LPAR5, which was highly correlated with prognosis and metastasis. And the expression of LPAR5 was positively correlated with immune cells, especially macrophages, indicating LPAR5+ macrophages played an important role in tumor microenvironment of osteosarcoma. Meanwhile, the genes in LPAR5 high expression group were enriched in immune-related activities and pathways, and differentially expressed genes between LPAR5+ macrophages and LPAR5- macrophages were enriched in the biological processes associated with phagocytosis and antigen presentation. What’ more, we found that LPAR5 was mainly expressed in TME, and high LPAR5 expression predicting a better prognosis. Conclusion We identified a TME-related gene, LPAR5, which is a promising indicator for TME remodeling in osteosarcoma. Particularly, LPAR5+ macrophages might have great potential to be a prognostic factor and therapeutic target for osteosarcoma.